(NsBORNIK kOMNOZITOROW(B-(Nsps(B.: (NlI^NOSTIs - (N`(B. (NbELEJKIJs (NGLAWNIJ REDAKTOR SERIIs; (Nn(B.(NkRAWCOWAs (NREDAKTORs ((NsANKT(B-(NpETERBURGs (NlI^NOSTIs, 2018)
(Nw SBORNIK kOMPOZITORY WO[LI DWENADCAT_ BIOGRAFI^ESKIH O^ERKOW(B,(NGEROQMI KOTORYH STALI(B: (NiOGAN sEBQSTIQN bAHA I DRUGOJ KOMPOZITOROW(B.s
Keywords: (NkULTURAs